Free Trade Agreements: Singapore legal developments - HSU, Locknie (Institutional Knowledge at Singapore Management University, 2015)
Singapore has entered into a number of bilateral Free Trade Agreements (FTAs) with its trading partners. These FTAs vary in scope and commitments. As a result, Singapore’s legal environment and laws have seen some changes. Many of these changes would interest those who do business with or invest in Singapore. While this section does not attempt to provide comprehensive information on all changes resulting from treaty commitments, it highlights salient changes for those trading or investing in Singapore. The developments highlighted here include changes made to Singapore legislation, as well as legal commitments made by Singapore as a result of its treaty obligations. Users are advised to consult the texts and related documents of each FTA for a full appreciation of the benefits that they or their countries may be eligible for. Information about Singapore’s concluded agreements, and agreements still under negotiation, can be found here.